Benin : Ex Post Assessment of Longer-Term Program Engagement-An Update. (IMF Staff Country Reports; Country Report, 2011)
Benin, a member of the CFA franc zone, has experienced uneven economic progress over the last several decades. It has a long history of engagement with the IMF. This ex post assessment update covers primarily the implementation of the program supported by the 2005-09 poverty reduction growth facility (PRGF) arrangement. In the fiscal area, the overall objective was to increase poverty-reducing spending while maintaining the sustainability of public debt. Prior to the global financial crisis, Benin's economic growth accelerated steadily. External shocks explain some of the growth's underperformance.